Comparison of Inhibition Zones Between Butterfly Pea Flower (Clitoria ternatea) and Lemongrass (Cymbopogon citrarus) Against Streptococcus mutans and Staphylococcus aureus - Steven Martin Haditio; Zulfan Muttaqin; Lina Hadi (Fakultas Kedokteran Universitas Sriwijaya, 2021)
This study aims to determine the comparison of the inhibition zone between the extract of butterfly pea flower and lemongrass, against the bacteria streptococcus mutans and staphylococcus aureus. The samples that will be used in this research are streptococcus mutans and staphylococcus aureus bacteria. Data analysis used normality test and statistical test was performed using ANOVA analysis test and post hoc test. The results showed that there was no difference in the inhibition zone of butterfly pea flower extract against streptococcus mutans bacteria and lemongrass extract against streptococcus mutans. There was diffe rence in the inhibition zone between butterfly pea flower extract against staphylococcus aureus bacteria and lemongrass extract against staphylococcus aureus bacteria. Butterfly pea flower extract has a good inhibition zone in staphylococcus aureus bacteri a. Lemongrass extract has the same inhibition zone against both types of bacteria